Civil engineering - Fidler, T. Claxton 1841-1917 (Methuen, 1905)
Aimed at 'busy men' rather than engineers, this book on civil engineering is nontechnical. The author outlines the principles of civil engineering, the ordinary occupations of a civil engineer, and the subject of engineering.
Keywords: Civil engineering.; elektronické knihy; electronic books